Essays on life itself - Rosen, Robert, 1934-1998 (Complexity in ecological systems series., 2000)
Compiling twenty articles on the nature of life and on the objective of the natural sciences, this remarkable book complements Robert Rosen's groundbreaking Life Itself?a work that influenced a wide range of philosophers, biologists, linguists, and social scientists. In Essays on Life Itself, Rosen takes to task the central objective of the natural sciences, calling into question the attempt to create objectivity in a subjective world and forcing us to reconsider where science can lead us in the years to come.